Effect of Monosaccharides and Disaccharides Type on Ionic Conductivity of Liquid Electrolyte Based Lithium Iodide - Ra'il, Nur Hani; Mobarak, Nadhratun Naiim (Universitas Andalas, 2021)
Liquid electrolyte was prepared by dissolving glucose, fructose, sucrose and lactose separately with different percentage of lithium iodide (10 – 35%) in aqueous solution of 1% acetic acid. Liquid electrolyte is characterized using conductivity meter to determine ionic conductivity. Computer simulations of Density Functional Theory (DFT) was used to identify the dominant functional groups on monomers such as glucose, sucrose, fructose and lactose when interact with the lithium salt by using B3LYP/6-31G ++ (d, p) basis set. The highest ionic conductivity for monosaccharide is glucose at 28.20 mS/cm while for disaccharide is lactose at 28.00 mS/cm with percentage of salt at 35 wt.%. Ionic conductivity increases when concentration of salt increase because there is an interaction between salt with functional groups of compounds. Based on computer simulations of DFT, interaction between lithium with compounds can be occurred due to negative electrostatic potential on the molecule. Electronegativity value of oxygen atom in glucose (-0.562e) and lactose (-0.567e) higher than fructose (-0.559e) and sucrose (-0.515e). Functional groups that are dominant to interact when interact with lithium salt are O-15 for glucose and O-17 for lactose due to the shorter bond length, the stronger energy attraction between functional groups with lithium.